Maximum Analysis of Human Resource Availability Units in the Construction of the Banjar Wongaya Betan Tabanan Multipurpose Center - Ritaka Wangsa, Anak Agung Ratu; Mirayani Pradnyadari, Ni Luh Made Ayu; Sapta Widana, I Nengah (Universitas Pendidikan Nasional, 2025)
Human resources are very important in the implementation of construction projects. Improper allocation of human resources can lead to overallocation of human resources, which reduces work productivity. In the time schedule report for the realization of the Banjar Wongaya Betan Multipurpose Hall Development Project in Tabanan Regency, there was a discrepancy between the actual progress and the planned progress, resulting in delays in implementation. Based on these issues, research was conducted to determine the comparison between the maximum unit requirements and availability before and after Resources Leveling was carried out using Microsoft Office Project 2019. Based on the analysis results, it was found that the number of human resources that were initially over-allocated could be optimized after the leveling process was carried out using the resources leveling method with Microsoft Office Project 2019. The total human resource requirements and availability, which were initially 48.26 people and 37 people, became 32.13 people and 37.00 people after leveling, which means that human resources are sufficient for project implementation. The leveling results data can be used as evaluation material and benchmarks for subsequent projects.